Pengembangan Media Pembelajaran Berbasis Schoology untuk Meningkatkan Hasil Belajar Siswa Kelas V SD - Efriani, Yola Monica; Zainil, Melva (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
The use of technology in the industrial revolution era 4.0 is a challenge as well as an opportunity to improve the quality of learning. One of the uses of technology in learning is the creation of schoology media . This study aims to developing shoology–based solids learning media  wich are valid, practical, and effective to improve the fifth year elementary school students’ learning outcomes.This study used a research and development method with Plomp model wich consisted of three stages: preliminary research, development and prototype phase and assessment. This study was conducted in SDN 08 Padang Besi, Padang. The data were collected using test and no-test techniques. The results of this study indicate that developed learning media is valid with a validity level of 88,02% and practicality students respons with a practicality level of 95% and teacher respon with a practicality level of 95,83%. Furthermore, it was found using schoology media has a significants impact on the students’ learning outcomes. The results of the t-test  show that  > , or 8,026 > 2,145. Moreover, the effectiveness of schoology media makes 80% of the students reach KKM.